Finance and Development, December 1969. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1969)
This paper focuses on telecommunication development in Ethiopia. The paper highlights that there are now over 20,000 telephones in Addis Ababa (in 1969), but the demand for service still exceeds the supply. About 800 installation requests are received each quarter; of these, 600 can be fulfilled. Ethiopia's annual telephone growth rate has averaged 17 percent over the past six years. Though long-distance lines have been expanded by 125 percent since the early 1950s, the interurban network between Addis Ababa and the rest of the country is seriously overloaded.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet